Cold War statesmen confront the bomb nuclear diplomacy since 1945 - Gaddis, John Lewis; Oxford eBooks (Oxford : Oxford University Press, 1999)
This text uses biographical techniques to test the question: did the advent of the nuclear bomb prevent World War III? It examines the careers of ten Cold War statesmen, and asks whether they viewed war, and its acceptability, differently after the advent of the bomb.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nuclear arms control; Cold War; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; Electronic books